The value of dehydrated alfalfa and delayed grain fed to young cows on winter bluestem - B.W. Swanson; E.F. Smith; D. Richardson; C.L. Drake (Kansas Agricultural Experiment Station Research Reports, 1969)
This test was to compared the following three winter treatments for young cows on bluestem pasture. Treatment 1 -- One pound of soybean oil meal and 2 pounds of ground sorghum grain per head daily during the entire winter feeding period. Treatment 2 -- One and a half pounds of soybean meal fed per heifer daily until 50 days before the feeding season ended, then ground sorghum grain was fed. The same total amount of sorghum grain as fed under treatment 1 throughout the winter was concentrated during the last 50 days with the soybean oil meal discontinued when grain feeding reached the quantity to supply the same amount of protein as those on treatment 1 received. Treatment 3-- Dehydrated alfalfa fed at 3.3 pounds and ground sorghum grain at 1 pound per heifer daily during the entire winter feeding period.
Keywords: Cattlemen' s Day; 1969; Report of progress (Kansas State University. Agricultural Experiment Station); 529; Beef; Dehydrated alfalfa; Grain; Winter bluestem